Maternal and Fetal Outcome in Patients with Pregestational Diabetes Mellitus and Gestational Diabetes Mellitus and Their Comparison with Non-diabetic Pregnancy (BIRDEM Medical Journal, 2016)
Objectives: To describe the maternal and fetal outcome in pre-gestational diabetes mellitus and gestational diabetes mellitus and to compare with that of non-diabetic pregnancies.Methods: This cross-sectional study was done in the Department of Obstetrics and Gynaecology of BIRDEM over one year period. Study population were divided in three groups; Group A pre-gestational diabetes, Group B gestational diabetes and Group C non-diabetic patients.Results: Each group had 50 patients. Majority of the patients were multigravida and delivery was at term. Caesarean section was common, 84% in group A, 76% in group B and 72% in group C. Post-partum haemorrage was the commonest maternal complication occurring in 24%, 22% and 22% cases in group A, B and C respectively. Common neonatal complications were respiratory distress syndrome (59.6%, 59.2% and 35% cases of group A, B and C respectively) and hyperbilirubinaemia (95.7%, 73.5% and 85% of cases of group A, B and C respectively). Neonatal hypoglycaemia occurred in 27.7% cases of group A and 18.4% cases of group B. No neonatal hypoglycaemia occurred in nondiabetic group.Conclusion: Incidence of post-partum haemorrhage, respiratory distress syndrome, neonatal hyperbilirubinaemia and hypoglycaemia were more in pre-gestational diabetes group than GDM group than non-diabetic group.Birdem Med J 2015; 5(1): 9-13